1999
DOI: 10.1144/0050421
|View full text |Cite
|
Sign up to set email alerts
|

Structural setting, geological development and basin modelling in the Rockall Trough

Abstract: Evidence from wide-angle seismic data in the Irish sector of the Rockall Trough suggests that the basin is underlain by thinned continental crust which has undergone differential stretching. The upper crust has been thinned by a stretching factor of 8-10 while the middle and lower crust (and probably also the lithospheric mantle) was stretched by a factor of 2-3. The latter figure is suggested as being representative of the overall lithospheric stretching. Crustal modelling fails to demonstrate any significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 32 publications
2
47
0
Order By: Relevance
“…Therefore, RAPIDS line 1 (Vogt et al 1998;Shannon et al 1999) is shown in Figure 4c as a landward extension of line CAM77. The two lines are separated by 140 km, which may explain the difference in the crustal thickness where the models are joined.…”
Section: Conjugate Transects South Of Icelandmentioning
confidence: 94%
See 3 more Smart Citations
“…Therefore, RAPIDS line 1 (Vogt et al 1998;Shannon et al 1999) is shown in Figure 4c as a landward extension of line CAM77. The two lines are separated by 140 km, which may explain the difference in the crustal thickness where the models are joined.…”
Section: Conjugate Transects South Of Icelandmentioning
confidence: 94%
“…However, the resolution of the data is not sufficient to determine the COB based on the lower-crustal velocity distribution. Published Barton & White 1997) and RAPIDS line 1 (after Vogt et al 1998;Shannon et al 1999). The inset map displays the age of the oceanic crust (after Gaina 2014; cf.…”
Section: Greenland -Iceland -Faroe Ridgementioning
confidence: 99%
See 2 more Smart Citations
“…Funck et al (2008) identified an extension of the HVLC beneath the northern part of the Hatton Basin below crystalline crust about 10 km thick, and interpreted this to be due to magmatic additions to the crust rather than partial serpentinization of the upper mantle. Further south, a zone of HVLC has been detected beneath the Hatton continental margin, overlain by crust in which the lower layer has been completely attenuated (Vogt et al 1998;Shannon et al 1999). The HVLC can be traced southwards beneath the SDRs on Edoras Bank (Barton & White 1997).…”
Section: Hvlc Adjacent To the Ocean Marginmentioning
confidence: 98%